CONTROLLING GRINDING PROCESS PARAMETERS USING CENTRAL COMPOSITE DESIGN TO REDUCE SLIMES IN PHOSPHATE ORE BENEFICIATION - Gamal S. Abdelhaffez; Mohamed S. Abd-Elwahed; Mohammed Hefni (Rudarsko-geološko-naftni Zbornik, 2022)
Ultrafine particles resulting from the grinding operations of phosphate ore cause problems of air pollution, and of the beneficiation plants particularly, flotation cells and filtration units. Particles of less than 38 μm are one of the undesirable consequences of the phosphate ore beneficiation stage, where fine or ultrafine powder accounts for 10–30 percent of phosphate quantities and is regarded as a loss. Furthermore, maintaining additional amounts of phosphate by reducing these particles will provide several benefits, including minimizing the environmental implications of slime disposal and enhancing the economic impact of the phosphate ore beneficiation process. This paper aims to maximize the useful phosphate particles and reduce the slime instead of doing even more work with traditional techniques. This goal might be attained by increasing the percent of particles of the desired size of the phosphate (Target) during the grinding process by determining the optimal operational conditions, that will reduce the amount of slime. The central composite design (CCD) is used to identify the number of experiments to be evaluated and to create a predictive model to be used for determining the optimal operation parameters. As a result of the optimization process, a maximum Target of 87.6% was obtained at grinding conditions t (5.1 min), v (42.6%), s (81.2%), and c (50.7%). Where t, v, s, and c stand for grinding time, occupied volume of ball, rotational speed percent from critical speed (%) and solid concentration by volume (%) respectively.